Pengaruh Supervisi Akademik Kunjungan Kelas Terhadap Kompetensi Paedagogik Guru dalam Pengelolaan Kelas - Atun, Siti Rupik (JURNAL SINEKTIK, 2024)
The purposes of this research are analyzing the effect of academic supervision with class visitation and its strength to the pedagogic competency teachers’ in managing the class. This is an experiment research. The place of this research is in Kedungringin General Elementary School. The moment of this research is from February up to May of 2023. The independent variable (X) is the minister academic supervision with class visitation. The dependent variable (Y) is the pedagogic competency teachers in managing the class.  The population is 8 teachers. The tool of collecting data is questionnaire (polling). The technique of analyzing data is using Paired Sample t Test. The result of this research is academic supervision with class visitation has very strong and significant effect to the pedagogic competency teachers in managing the class. tcalculation on [-12,28] with  significance on 0,000 is bigger than ttable (1,894). Before the treatment (pretest), the pedagogic competency teachers’ is including on good enough category (C). After the treatment (posttest), the pedagogic competency teachers’ is including on good category (B).